Impact of Hyperbaric Oxygenation on Blood Antistaphylococcal Activity During Liver Resection - P. N. Savilov; S. Ya. Dyachkova; A. V. Turovsky; V. N. Yakovlev (Общая реаниматология, 2013)
Objective: to study the impact of liver resection (LR) and a hyperbaric oxygenation (HBO) session and their combination on blood antistaphylococcal activity. Material and methods. Experiments were carried out on 77 outbred albino rats (females) exposed to LR (15—20% of the liver weight) and HBO at 3 ata as a 50-min session once daily, which was used in the operated rats in the first 3 days after LR. Serum bactericidal activity against opportunistic (No. 1726) and pathogenic (No. 209) S.aureus strains and the ability of neutrophils and monocytes to absorb S.aureus 209 were studied. Results. restoring the serum bactericidal activity against S.aureus 1726, HBO used after LR enhances its activity against pathogenic S.aureus 209. By decreasing the inhibitory effect of LR on the ability of the liver to enrich blood with the neutrophils that actively phagocy-tize the staphylococcus, HBO eliminates the retention of the monocytes actively phagocytizing S.aureus 209 in the operated organ, by concurrently increasing the count of these cells in the arterial blood. HBO stimulates the rate of uptake of S.aureus 209 by neutrophils in the operated organism when the blood passes through the vessels of the portal system with the partial retention of these cells in the liver portion left after its resection. By selectively suppressing the humoral component of blood antistaphylococcal defense, HBO in healthy unoperated animals stimulates the ability of the liver to enrich the blood with the monocytes that actively phagocytize the staphylococcus. At the same time the rate of uptake of S.aureus 209 by neutrophils is stimulated by hyperoxia. Conclusion. HBO regulates blood antistaphylococcal activity changes in response to LR by exerting a selective effect on the bactericidal activity of the blood against the staphylococcus in rats. Key words: liver, resection, hyperoxia, bactericidal activity, blood, staphylococcus.